Analysis of the Effect of Emotional Intelligence, Time Management, and Academic Stress on the Learning Behavior of Accounting Students - Silitonga, Juliarta; Nabila, Talita; Sihombing, Dona; Luthfi, Muhammad; Rahmadayanti, Nabila; Arnita, Vina (Journal of Advances in Accounting, Economics, and Management, 2025)
The purpose of this study was to analyze the effect of emotional intelligence, time management, and academic stress on students' accounting learning behaviour. In college, effective learning behavior is essential to achieve optimal learning outcomes. The method used in this study is a quantitative survey that collects data through questionnaires distributed to accounting students at several universities. Data analysis was conducted using PLS (Partial Least Square). The research shows that emotional intelligence has a significant positive influence on learning behaviour, and students with high emotional intelligence tend to be better able to manage their emotions and motivation during the learning process. In addition, good time management also contributes positively to learning behaviour, so that students can manage their time effectively. On the other hand, academic stress was shown to have a significant negative impact, as high levels of stress can affect concentration and motivation to learn. The conclusion of this study highlights the importance of developing emotional intelligence and time management skills in accounting students and the need for strategies to reduce academic stress. Recommendations for future research are to consider interventions that can improve these three components to support better learning behaviour.